A Study on Determinants and Types of Sexual Violence: Understanding and Preventing Sexual Harassment in Different Settings (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Sexual violence implies that without your agreement someone else pushes or manipulates others into undesired sexual interaction. Some people may not agree to reasons that may include fear, age, disease, handicap, andor alcohol or other medicines. Either child, adolescents, and adults, or elderly, may suffer sexual violence. Those that abuse sexually may be families, trusted persons, or strangers. In this study we have discussed about the determinants of sexual violence, types of sexual violence with women, different types of sexual violence which is concluded that the best way to eradicate sexual harassment at work is via prevention.